2015
DOI: 10.1001/jamaophthalmol.2014.3616
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Layers Imaged by Fluorescein Angiography and Optical Coherence Tomography Angiography

Abstract: The retinal vasculature is involved in many ocular diseases that cause visual loss. Although fluorescein angiography is the criterion standard for evaluating the retina vasculature, it has risks of adverse effects and known defects in imaging all the layers of the retinal vasculature. Optical coherence tomography (OCT) angiography can image vessels based on flow characteristics and may provide improved information.OBJECTIVE To investigate the ability of OCT angiography to image the vascular layers within the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
1,009
1
47

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,450 publications
(1,074 citation statements)
references
References 27 publications
17
1,009
1
47
Order By: Relevance
“…This imaging modality allows visualization of the SCP in excellent detail, however, the intermediate and DCP are not seen. 7 With increasing scan speeds, high resolution tomographic data acquisition and use of phase variance or decorrelation signals from blood cells within the vasculature and three-dimensional images of the retinal vessels can be generated. Essentially, en face visualization, layer by layer of the retina, with its constituent vascular beds is now a reality permitting better clinicopathological correlations to be made even in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This imaging modality allows visualization of the SCP in excellent detail, however, the intermediate and DCP are not seen. 7 With increasing scan speeds, high resolution tomographic data acquisition and use of phase variance or decorrelation signals from blood cells within the vasculature and three-dimensional images of the retinal vessels can be generated. Essentially, en face visualization, layer by layer of the retina, with its constituent vascular beds is now a reality permitting better clinicopathological correlations to be made even in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, en face visualization, layer by layer of the retina, with its constituent vascular beds is now a reality permitting better clinicopathological correlations to be made even in vivo. 7 Recently, case reports and case series have imaged PAMM with OCTA-demonstrating areas of attenuation and pruning of the DCP. [8][9][10][11][12] However, little is known about the natural course of PAMM secondary to CRVO and no correlation between the natural course of the visual acuity and the extension of the DCP has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Spaide et al, [3] demonstrated that with detection of 12 eyes, fluorescein angiography couldn't visualize the radial peripapillary capillary network around the optic nerve head completely, whereas the network was visualized by the SSADA scans. Yali Jia et al, [4] used a highspeed (100,000 A-scans/sec) 1050 nm wavelength sweptsource optical coherence tomography (SS-OCT) to scanned five neovascular AMD and five normal eyes.…”
Section: Applications Of Octamentioning
confidence: 99%
“…Существует также возможность получать по-слойные карты плотности сосудов сетчатки с поква-дрантным расчетом значений плотности сосудов. В-сканы ОКТ могут регистрироваться одновремен-но с ОКТ-ангиограммами, поэтому можно увидеть точное местоположение патологического участка на соответствующих В-сканах [22,23]. Достоинством ОКТ-А является возможность визуализации как ре-тинальной, так и хориоидальной микрососудистой сети, тогда как ФАГ позволяет "видеть" только со-суды сетчатки, а ИЦЗА больше подходит для иссле-дования сосудистой оболочки.…”
Section: окт-ангиография (окт-а)unclassified